The dinoflagellate cyst Molassedinium bicornutum gen. et sp. nov. from the Oligocene of the North Alpine Foreland Basin, Austria. (2nd October 2019) - Soliman, Ali; Slimani, Hamid
Abstract: The organic-walled dinoflagellate cyst Molassedinium bicornutum gen. et sp. nov. described in this paper is recorded in the Oligocene (Rupelian) organic-rich sediments of the Eggerding Formation from the North Alpine Foreland Basin (Molasse Basin), Austria. It was discovered within a diverse and well-preserved dinoflagellate cyst assemblage. It is a gonyaulacacean (leptodinioidean) holocavate cyst with distinctive apical and antapical ectophragmal horns and an apical archaeopyle. The current stratigraphic range of the taxon is restricted to the Rupelian. It may constitute a potentially important regional stratigraphic marker for high-resolution age control. It is associated with a dinoflagellate cyst assemblage indicating inner–outer neritic and nutrient-rich environments.